Ultrasound-Guided Combined Femoral and Popliteal-Sciatic Nerve Block for Foot Debridement in a Patient with Peripheral Arterial Disease, Heart Failure with Reduced Ejection Fraction, and Pulmonary Oedema: A High-Risk Case Report - Heri Dwi Purnomo; Paramita Putri Hapsari; Muhammad Rizal Aulia (Open Access Indonesian Journal of Medical Reviews, 2026)
Peripheral arterial disease (PAD) in its advanced stage leads to critical limb ischaemia requiring operative debridement, and coexisting heart failure with reduced ejection fraction (HFrEF) and pulmonary oedema make general and neuraxial anaesthesia hazardous. We describe a 59-year-old man with three-vessel coronary artery disease previously treated by multiple percutaneous coronary interventions, HFrEF (ejection fraction 36%), hypertension, diabetes mellitus and bilateral PAD who presented with acute decompensated heart failure, pulmonary oedema and bilateral pleural effusion together with an extensive left foot ulcer requiring urgent debridement and necrotomy. An ultrasound-guided combined femoral and popliteal-sciatic nerve block was performed using 20 mL of 1.5% lidocaine and 20 mL of 0.25% bupivacaine. The patient remained conscious and haemodynamically stable with systolic blood pressure 90–110 mmHg, heart rate ~85 beats/min and SpO₂ 100%. The 60-minute procedure was uneventful with no local anaesthetic toxicity, new neurological deficit or respiratory compromise, and the patient was transferred to the high-care unit. Ultrasound-guided peripheral nerve blockade represents a cardiopulmonary-sparing anaesthetic strategy that can deliver adequate operating conditions for lower-extremity surgery in patients with PAD and severe cardiac and respiratory comorbidity. Keywords: Peripheral nerve block, Peripheral arterial disease, Heart failure with reduced ejection fraction, regional anesthesia, ultrasound guidance.